Biopsychosocial Factors Affecting Quality of Life in Post-stroke Patients: A Path Analysis Evidence from Surakarta Hospital, Central Java - Maki Zamzam; Didik Gunawan Tamtomo; Vitri Widyaningsih (Masters Program in Public Health, 2020)
Background: Basic health research shows that the prevalence of non-communicable diseases has in